The Role of the Indonesian Ulema Council in Establishing Fatwas as a Method of Ijtihad in the Contemporary Era - Ikhsana, Lisa; Khasanah, Eka Imroatun (Jurnal Scientia Indonesia, 2020)
The Indonesian Ulama Council is an independent institution to establish fatwas in Indonesia which is based on the test of ijtihad. Today, the fatwa designated by the Indonesian Ulama Council must adjust to the developments in accordance with the contemporary era. But its implementation, the various fatwas that have been set sometimes causing controversy from parties that have unequal interpretation and different interests. Like is the fatwa Number 31 of 2020 concerning Committee Jum'at and Jemaah Prayers for Preventing Transmission of the Covid-19 Outbreak and haram cryptocurrency fatwas invite various pro and counters. The method used in this research is a juridical Islamic legal approach so that the presentation of the results and descriptive form of analysis. Fatwas that correspond to contemporary ages should always be guided by strict sources according to Islamic legal sources as guidance of life people. Then it will be discussed more detailed about the Indonesian Ulama Council and MUI fatwa relevance to the contemporary era.